User Satisfaction with Application for Postpartum Maternal Gymnastics (SIMPOR) - Lubis, Astri Yulia Sari; Abilowo, Ashar (Babali Publisher, 2024)
Introduction: Bleeding is the main cause of 50%-60% morbidity and mortality in the postpartum period due to imperfect myometrial contraction. Postpartum exercise is one of the actions of maximizing uterine contractions. It's accelerate uterine involution. Technology development very fast today, improvement of postpartum android base application that's applicable, educative and informative is needed. This study aims to develop a postpartum maternal exercise application (SIMPOR) for postpartum mothers using Android then test them until obtaining descriptions about satisfaction with the SIMPOR application. Methods: This study used a Research and Development method (R&D) with 152 respondents taken by proportional stratified random sampling. Data analysis was chi-square with univariate and bivariate. Results: The majority of participants were aged in 20-40 years old (98%), educational majority in higher education (59.9%), most of the respondents were housewives (65.8%), having more than one toddler (77.6%), and the average of toddler age was less than 2 years old (84.2%). Most of the respondents' satisfaction with the SIMPOR application was very satisfied (88.16%); 3) There was a relationship between mother's work, parity, and the smallest child age on the satisfaction of using the SIMPOR application with pvalue<0.05. Conclusion: Participants were very satisfied with this SIMPOR application. Based on that result, hopefully postpartum mothers can use this application as postpartum exercise guidance and to monitor their process postpartum period involution.